Characterization and development of microsatellite markers for Echinomastus johnsonii and congeneric taxa - Zumwalde, Bethany A. (Appl Plant Sci, 2019)
PREMISE: Microsatellite markers were developed in Echinomastus johnsonii (Cactaceae) for use in several morphologically similar, closely related taxa within the genus to study genetic structure and diversity within and among individuals and populations. METHODS AND RESULTS: Using reads from shallow, whole genome Illumina HiSeq high‐throughput sequencing, we developed and characterized 15 microsatellite primer pairs for E. johnsonii, E. erectocentrus var. erectocentrus, E. erectocentrus var. acunensis, and E. intertextus. Of the 15 microsatellite markers, 14 amplified successfully and were polymorphic in three of the four taxa tested, with the exception of three markers in E. intertextus. In E. johnsonii, the number of alleles ranged from one to 15 and levels of observed and expected heterozygosity ranged from 0.000 to 1.000 and 0.000 to 0.917, respectively. CONCLUSIONS: These markers will be useful for investigating population genetics and clarifying taxonomic relationships of E. johnsonii and congeneric species.